Synthesis, characterization and photo catalytic degradation of aqueous eosin over Cr containing Ti/MCM-41 and SiO2-TiO2 catalysts using visible light - Awate, S. V.; Jacob, Nalini E.; Deshpande, Suvarna S.; Gaydhankar, T. R.; Belhekar, Anagha A. (Journal of Molecular Catalysis A - Chemical, 2005)
Two series of samples were prepared namely Cr-Ti/MCM-41 and Cr/SiO2-TiO2 keeping Si/Ti mole ratio same, with different Cr loading. The physico-chemical properties of the samples were characterized by different analytical techniques such as XRD, FTIR, TEM, low temperature N-2 sorption, and UV-vis diffused reflectance spectroscopy. The impregnated TiO2 was in anatase form. The crystallite size was determined from Scherrer equation as well as by TEM. There is a difference between the shapes of nitrogen adsorption isotherms with and without Cr-loaded Ti/MCM-41 samples. The rate of nitrogen adsorption was found to increase with decrease in Cr content at lower P/P-0 for Cr-Ti/MCM-41 samples due to the blocking of the pores with Cr. All MCM-41 samples exhibited pore sizes from 24 nm to 32 nm. UV-vis diffused reflectance spectra of all Cr-loaded samples showed red shift of their absorption edges. Photo degradation of eosin dye was studied using visible light. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Cr-Ti/MCM-41; Cr/SiO2-TiO2; eosin; photo degradation; visible light

Textural/structural, stability and morphological properties of mesostructured silicas (MCM-41 and MCM-48) prepared using different silica sources - Gaydhankar, T. R.; Taralkar, U. S.; Jha, Ratnesh Kumar; Joshi, P. N.; Kumar, R (Catalysis Communications, 2005)
A series of MCM-41 and MCM-48 samples have been synthesized under hydrothermal and static conditions using different silica sources (fumed silica, silica sot and ethyl silicate) and characterized by powder XRD, scanning electron microscopy and N-2 adsorption. The silica source reactivity trend observed was as: ethyl silicate > fumed silica > silica sot. However, the extent of contraction caused by calcination, magnitude of the wall thickness and stability were found to depend not only upon the type of silica source used but also on the type of structure formed. Noticeable morphological differences were observed in case of only MCM-41 when silica sources were varied. © 2005 Elsevier B.V. All rights reserved.

Hydrothermal synthesis of MCM-41 using differently manufactured amorphous dioxosilicon sources - Gaydhankar, T. R.; Samuel, V.; Joshi, P. N. (Materials Letters, 2006)
The influence of differently manufactured amorphous dioxosilicon sources such as fumed silica (FS), spray dried precipitated silica (PSI) and flash dried precipitated silica (PS,) on the course of structural development and properties of hydrothermally prepared siliceous MCM-41 phases have been investigated. Powder XRD, N-2 adsorption/desorption and scanning electron microscopy techniques were used for sample characterization. On the basis of results obtained from time dependent study on the progressive development of MCM-41 mesophases, the reactivity trend of dioxosilicon sources observed was as: FS > PS1 > PS2. MCM-41 synthesized using least expensive PS2 having less surface area has exhibited thicker pore walls but poor orderness, while MCM-41 prepared from expensive FS having high surface area has thinner pore walls and was well ordered. The extent of contraction caused by calcination, magnitude of the wall thickness and structural stability were found to be dependent on manufacturing process of dioxosilicon sources. The noticeable morphological differences were also observed by variations in the type of dioxosilicon sources used in the hydrothermal synthesis MCM-41 materials. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Characterization; dioxosilicon sources; Hydrothermal synthesis; MCM-41; porosity; Structural stability

Influence of starting precursors and synthesis methods on the physiochemical properties of zirconia - Gaydhankar, T. R.; Jha, Ratnesh Kumar; Nikalje, M. D.; Waghmare, K. J. (Materials Research Bulletin, 2014)
Under identical and judiciously pre-optimized synthesis conditions, the influence of different combinations of zirconium sources and/or post treatment conditions on structural properties, thermal stability, phase composition and morphology of zirconia has been investigated. High surface area tetragonal zirconia could be synthesized in a cost-effective manner from 1 M solution of zirconium oxynitrate at pH 11 using aqueous ammonia solution as a precipitant when calcined at 400 degrees C for 3 h. Irrespective of the preparation method, pH and starting precursor, zirconia samples prepared without digestion contained dominant monoclinic phase with some traces of tetragonal phase when calcined at 700 degrees C. Even though there is linear decrease in surface area with increase in the crystallite size for each sample as a function of calcination temperature, no co-relation between the surface area and crystallite size could be achieved. SEM images show agglomerated and irregular shape particles between 10 to 20 mu m. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Oxides; Sol-gel chemistry; Thermogravimetric analysis (TGA)